Effective implementation of relationship orientation in new product launches - Matikainen M; Terho H; Matikainen E; Parvinen P; Juppo A (Elsevier Inc., 2022)
The critical role of relationships in business performance is widely recognized in the business marketing literature. However, to date, the prevailing new product launch research has concentrated on firms' general customer and competitor focus on predicting launch performance, and mainly applied a product centered or marketing mix perspective on considering effective strategic and tactical launch activities. Consequently, there is only scant knowledge on the relevance of a relational perspective when launching new products. The study contributes to this gap by examining the impact of firms' relationship orientation on launch performance and the key activities through which it is transformed into performance in the new product launch context. A set of hypotheses is developed and tested with data collected from 109 new product launches in pharmaceutical companies. The results show that sales force management and relationship leveraging mediate relationship orientation's impact on launch performance through complexly intertwined relationships. From a theoretical perspective, this study highlights the role of the relational perspective in new product launch and fosters our understanding on how relationship-focused culture is effectively implemented in practice. From a managerial perspective, the results offer insights on how firms can effectively enhance the successful commercialization of new products through relationship-oriented sales and marketing activities.